Continuous Essential Oil and Oleoresin Extraction from Star Anise (Illicium verum) by Hydrodistillation and Solvent Extraction - Miranda, Fitri Ariadna Sodi; Iftitah, Elvina Dhiaul; Warsito, Warsito; Berliana, Adilatunnisa Nur Indah; Seta, Fadhlih Arya (Indonesian Green Technology Journal, 2022)
Star anise (Illicium verum) is widely used as a medicinal herb and spice. The extracts, essential oil and oleoresin, can be cici4d produced by hydro-distillation and steam distillation, while solvent and supercritical fluid extraction can be used to extract oleoresin. In this work, the star anise is distilled to obtain the oil, subsequently, its residue is extracted by solvent extraction to get the oleoresin. Whole and grounded star anise fruit is distilled by hydro-distillation for 8, 12, 16, 20, and 24 hours, thus the highest yield is obtained at 20 hours from grounded fruit, and the highest trans-anethole content of 68.50% is obtained at 8 hours from grounded fruit. Residue from the whole fruit-distillation process is extracted by Soxhlet extraction with three types of solvent (ethanol, diethyl ether, and n-hexane) for 6 hours. The highest yield was obtained from ethanol extraction with 1.16% yield and the highest content of trans-anethol was obtained from n-hexane fraction. One sample with the highest content of anethole from whole and grounded fruit-distilled oil and oleoresin are picked, and later they are tested to cici4d measure their antioxidant capacity by Ferric Reducing Antioxidant Power Assay (FRAP). Keywords: Essential oil, oleoresin, star anise, trans-anethole